2018
DOI: 10.28991/cej-030961
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the Spatial Flooding Intensity with Unit Flood Response Method in the Tangrah Watershed, Iran

Abstract: Increased flooding in recent years indicates that most parts of the country are subjected to periodic and destructive flood attacks. Therefore, the identification of high-risk areas with potential runoff production within a watershed area is one of the most important measures in flood control and reduction of the damage caused by it. In this study, the quasi-distributional ModClark method was employed to simulate the hydrograph of flooding, and the unit flood response method was applied to determine the intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Kumari and Goel (2015) adopted the SUH approach for flood estimation for rivers of Saurashtra Region contributing into Gulf of Khambhat. Gharib et al (2017) made an attempt to simulate the flood hydrograph of Tangrah catchment, a tributary of Madarsoo basin in Golestan province in northeastern Iran through semi-distributed version of the modified Clark method. Kim and Mun-Ju Shin (2018) developed the relationship between the parameters such as runoff coefficient, intensity of rainfall and curve number, and then utilized the relationship to calculate the peak flow using the rational formula for ungauged catchments.…”
Section: Introductionmentioning
confidence: 99%
“…Kumari and Goel (2015) adopted the SUH approach for flood estimation for rivers of Saurashtra Region contributing into Gulf of Khambhat. Gharib et al (2017) made an attempt to simulate the flood hydrograph of Tangrah catchment, a tributary of Madarsoo basin in Golestan province in northeastern Iran through semi-distributed version of the modified Clark method. Kim and Mun-Ju Shin (2018) developed the relationship between the parameters such as runoff coefficient, intensity of rainfall and curve number, and then utilized the relationship to calculate the peak flow using the rational formula for ungauged catchments.…”
Section: Introductionmentioning
confidence: 99%
“…Although Iraq is a developing country, where statistics and data are rarely available, there are some convenient flood models which can solve these constraints [18]. For instance, Gharib et al (2017) [15] and Patel & Joshi (2017) [17] showed in their studies that the lack of availability of data can be avoided by adopting computer software for flooding simulation. For examples, GIS, Global Mapper, Artificial Neural Network (ANN), and rainfall-runoff modelling that can be used in specifically in developing countries, due to its simplicity and efficiency.…”
Section: Introductionmentioning
confidence: 99%